Implikasi Kegiatan Safari Mahasiswa UKMK LPTQ&D UIN Raden Fatah Palembang: Studi Pengembangan Karakter - Kgs. M. Roihan Adnan; Subiyantoro Subiyantoro (Jurnal Pengabdian Pada Masyarakat, 2022)
STUDENTS’ IMPLICATIONS FOR SAFARI ACTIVITIES OF UKMK LPTQ&D UIN RADEN FATAH PALEMBANG:CHARACTER DEVELOPMENT STUDIES. In today's social life there are still many unresolved problems in the field, one of which is a moral crisis such as promiscuity, crimes against friends, theft, cheating habits, drug abuse, pornography and vandalism. The moral crisis will poison generations, especially students. To overcome these problems among students, namely the need for character education in universities. The purpose of this study is to identify the implications of student safari activities for UKMK LPTQ&D UIN Raden Fatah Palembang and describe the implementation of the student safari activities. The research method used is descriptive qualitative and makes UKMK LPTQ&D UIN Raden Fatah Palembang the object of research. Collecting data through interviews and documentation (primary data) and books, journals or other articles (secondary data) and analyzing data by integrating the results of interviews with other journals, books or articles and then made an interpretation. The result is that the implications of the student safari activities of UKMK LPTQ&D UIN Raden Fatah Palembang in character development studies are developing religious character, respecting achievement, responsibility, friendship/communicative and cooperation. The activities in implementing the student safari activities of UKMK LPTQ&D are tadarusan, lectures ramadhan, teaching religious materials in schools, holding competitions and torch parades.